2023
DOI: 10.3390/v15071474
|View full text |Cite
|
Sign up to set email alerts
|

Metaviromic Characterization of Betaflexivirus Populations Associated with a Vitis cultivar Collection in South Africa

Abstract: South Africa is associated with a centuries-old viticultural industry, accompanied by a diverse range of wine and table grape cultivars and an extensive history of pervasive introductions of vine material and associated viruses. The Vitis D2 collection in Stellenbosch represents the most comprehensive collection of Vitis species, hybrids, and cultivars in South Africa. We collected leaf petiole material from 229 accessions from this collection. Our metaviromic analyses revealed a total of 406 complete/near com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…For example, screening of autochthonous cultivars from the Balearic Islands (Spain) has shown that more than 52% of the grapevines are affected by a mixed viral infection, with the economically significant GLRaV-3 and GFLV being some of the most common viruses [19]. A metaviromic study of betaflexiviruses in the South African ampelographic collection has also revealed a predominance of multiple virus infections, including economically significant viruses [20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, screening of autochthonous cultivars from the Balearic Islands (Spain) has shown that more than 52% of the grapevines are affected by a mixed viral infection, with the economically significant GLRaV-3 and GFLV being some of the most common viruses [19]. A metaviromic study of betaflexiviruses in the South African ampelographic collection has also revealed a predominance of multiple virus infections, including economically significant viruses [20].…”
Section: Introductionmentioning
confidence: 99%